Bovatec® vs. Rumensin® fed in free-choice mineral-grain mixtures on early intensively grazed, native grass - F. Brazle; Gerry L. Kuhl (Kansas Agricultural Experiment Station Research Reports, 1986)
The performance of grazing heifers offered a free-choice mineral or two mineral-grain-ionophore mixtures was evaluated in 3-year study. Heifers ate more of the supplement containing Bovatec® than that containing Rumensin® (P<.05). Heifers fed Bovatec® gained faster (P<.10) than those fed Rumensin® or the control mineral mixture.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Mineral-grain; Native grass